2012
DOI: 10.1002/uog.9076
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of aortic isthmus Doppler in appropriately grown and small‐for‐gestational‐age fetuses with normal and abnormal umbilical artery Doppler

Abstract: Objective To establish reference ranges using longitudinal data for aortic isthmus (AoI)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 27 publications
1
19
0
2
Order By: Relevance
“…The direction of systolic AoI blood flow is thus determined by the comparative LV and RV stroke volumes along with the downstream vascular impedances [1]. In diastole, when the two semilunar valves are closed, the direction of AoI blood flow is determined purely by the balance of downstream vascular impedance in the brachiocephalic and placental and subdiaphragmatic circulation [15]. The AoI waveform can therefore be seen as the product of a complex interaction between (a) LV and RV ejection and (b) brachiocephalic plus placental and subdiaphragmatic vascular impedance.…”
Section: Physiologymentioning
confidence: 99%
See 3 more Smart Citations
“…The direction of systolic AoI blood flow is thus determined by the comparative LV and RV stroke volumes along with the downstream vascular impedances [1]. In diastole, when the two semilunar valves are closed, the direction of AoI blood flow is determined purely by the balance of downstream vascular impedance in the brachiocephalic and placental and subdiaphragmatic circulation [15]. The AoI waveform can therefore be seen as the product of a complex interaction between (a) LV and RV ejection and (b) brachiocephalic plus placental and subdiaphragmatic vascular impedance.…”
Section: Physiologymentioning
confidence: 99%
“…In normal fetuses antegrade flow is present in the first half of pregnancy in both systole and diastole of the AoI waveform due to low placental vascular impedance. The gradual deceleration of the systolic upstroke with a brief reversal of flow may be due to increasing RV dominance, coupled with the rise in placental impedance that occurs with gestation [1,14,15]. However, a large cross-sectional study (458 fetuses) found no correlation between AoI PI and umbilical artery (UA) PI, suggesting rather that they could be considered independent factors for fetal surveillance [11].…”
Section: Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…To date, several modalities have been commonly used to diagnose and monitor the deterioration of the affected fetuses . Myocardial performance index (MPI) or Tei index is a method of the Doppler echocardiography used to evaluate cardiac ventricular systolic and diastolic functions .…”
Section: Introductionmentioning
confidence: 99%